2021
DOI: 10.1136/bmjopen-2020-047016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patient characteristics, management and outcomes for COVID-19 at district hospitals in the Western Cape, South Africa: descriptive observational study

Abstract: ObjectivesTo describe the characteristics, clinical management and outcomes of patients with COVID-19 at district hospitals.DesignA descriptive observational cross-sectional study.SettingDistrict hospitals (4 in metro and 4 in rural health services) in the Western Cape, South Africa. District hospitals were small (<150 beds) and led by family physicians.ParticipantsAll patients who presented to the hospitals’ emergency centre and who tested positive for COVID-19 between March and June 2020.Primary and secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 19 publications
2
55
1
1
Order By: Relevance
“…Our search was limited by published full-text article in English language. Most studies investigating this association used BMI categories as the predictor variable [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Four cross-sectional studies did not specify the used classification of obesity [38][39][40][41] presumably using the WHO guidelines defining obesity as BMI of 30 or higher.…”
Section: Obesity and Covid-19 Disease Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…Our search was limited by published full-text article in English language. Most studies investigating this association used BMI categories as the predictor variable [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Four cross-sectional studies did not specify the used classification of obesity [38][39][40][41] presumably using the WHO guidelines defining obesity as BMI of 30 or higher.…”
Section: Obesity and Covid-19 Disease Severitymentioning
confidence: 99%
“…Four cross-sectional studies did not specify the used classification of obesity [38][39][40][41] presumably using the WHO guidelines defining obesity as BMI of 30 or higher. Outcome variables included: hospitalization [36,38,42], ICU admission [31,35,37,38,[43][44][45], intubation [24,25,29,37,38], invasive mechanical ventilation [26,31,34], disease severity [27,28,30,33] and death [24][25][26][27][28][29]32,[38][39][40][41]. Of the eleven studies investigating the association between BMI and mortality in hospitalized COVID-19 patients, ten studies observed an increased mortality rate in patients that were overweight (BMI ≥ 25 to <30) [24,32], or suffering from obesity (BMI ≥ 30) [25,29,[38][39][40][41], or severe obesity (BMI ≥ 35) [26,…”
Section: Obesity and Covid-19 Disease Severitymentioning
confidence: 99%
“…Countries across the globe have erected field hospitals to support permanent medical facilities during the ongoing novel coronavirus disease (COVID-19) pandemic [ 1 , 2 , 3 , 4 , 5 , 6 ]. Often enacted by provincial or territorial health ministries, these facilities addressed the growing limitations of bed capacity, especially for non-critical care patients [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that Africa consists of relatively young populations, with active community health structures educated in pandemics and favorable climate, the COVID-19 outbreak brought a notable growth of hospital workload affecting patient management. 13 Despite the reduction of patient visits, the increased demands for critically ill patients in understaffed intensive care units result in significantly less time dedicated to non-COVID-19 patient care, 14 while the landscape of public restrictions for the deterioration of the COVID-19 pandemic is rapidly evolving with disproportional effects among rural and urban areas. The collateral political damages from incidents of police enforcement abuse and brutality in South Africa with regard to racial discrimination, the assignment of police authorities from the government to people in Ghana, in conjunction with economic recession might cause a new exacerbation of YF in African regions.…”
mentioning
confidence: 99%